Role of Serial C-reactive Protein (CRP) in Relation to Total Leucocyte Count, Platelet Count & Blood Culture for early Diagnosis of Neonatal Septicemia in Developing Countries - Barua, Chiranjib; Anwar, Md Nurul; Shahidullah, Md; Hossain, Shahadat; Barua, Sharmila; Chowdhury, Nobel (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Neonatal septicemia is a clinical syndrome of systemic illness accompanied by bacteremia occuring in the first 28 days of life. Neonatal septicemia is one of the major causes of neonatal death in developing countries. Early diagnosis and treatment can prevent neonatal mortality and morbidity. The present study includes: 1) usefulness of CRP (C-reactive protein), Total Leucocyte Count, Platelet Count and Blood Culture in early diagnosis of Neonatal Sepsis, 2) significance of serial CRP in diagnosis of neonatal sepsis. 3) the prognostic value of CRP in neonatal sepsis. This is a prospective study done in neonatal ward, Chittagong Medical College Hospital and carried out from January 2008 to January 2011. Sample size was 300. One hundred fifty neonates with suspected sepsis as cases and 150 healthy babies as control were enrolled in this study. Seventy two percent of cases neonates were preterm and low birth weight. Common risk factors for neonatal septicemia which were identified in this study; preterm (72%), low birth weight (72%), premature rupture membrane (60%), chorioamnionitis (26%) and maternal urinary tract infection (16%) . Out of 150 cases of suspected neonatal sepsis total 80.7%% had raised CRP, in initial sample 70.39% were CRP positive and in 2nd sample additional 9.31% case were CRP positive . In control group 91% were CRP negative. CRP was positive in 100% of culture proven sepsis. Sensitivity of CRP was 80.67% and specificity of CRP was 76.44%. Leucocytosis was observed in 7% of cases and leucopenia was found in 11% of cases. In 82 % cases leucocyte count was found normal. In control group, 95% had normal leucocyte count and 5% had leucocytosis but no leucopenia. Sensitivity of leucocyte count was 18% and specificity was 20.68%. Thrombocytopenia was found in 28% of case group. Out of 150 cases only 15.33% yielded growth of organisms in blood culture. Klebsiella was the most common pathogen isolated which was followed by E.coli and Strph. aureus. Sensitivity of blood culture was 15.33% and specificity was 100% Therefore serial CRP can be taken as alternative method for diagnosis of neonatal sepsis specially in developing countries where blood culture is not readily available. J Bangladesh Coll Phys Surg 2014; 32: 61-65